Is the Adolescent Brain at Greater Vulnerability to the Effects of Cannabis? A Narrative Review of the Evidence - Blest-Hopley, Grace; Colizzi, Marco; Giampietro, Vincent; Bhattacharyya, Sagnik (Frontiers in Psychiatry, 2020)
Cannabis use during the critical neurodevelopmental period of adolescence, may lead to brain structural, functional and histological alterations that may underpin some of the longer term behavioural and psychological harms associated with it. The endocannabinoid system performs a key regulatory and homeostatic role, that undergoes developmental changes during adolescence making it potentially more susceptible to the effects of exposure to cannabis during adolescence. Here, we synthesise evidence from human studies of adolescent cannabis users showing alterations in cognitive performance as well as in brain structure and function with relevant preclinical evidence to summarise the current state of knowledge. We also focus on the limited human evidence that cannabis use during adolescence poses a greater risk than use during adulthood, identify gaps in current evidence and suggest directions for new research. Preclinical evidence, further supports disruption from cannabis use being specific to the developmental period. Collectively, evidence suggests that adolescence onset cannabis use is associated with poorer performance in cognitive tasks, though, the extent to which these deficits persists following an adequate period of abstinence remains unclear. While, brain structural alterations do not show great consistency, brain functional alterations in cannabis users general suggest increased activation compared to non-users. Functional connectivity between brain regions and within known functional circuits is altered and may underlie the observed differences in brain activation, perhaps from inefficient recruitment of regions required for task performance. Such disordered organisation of brain circuitry during adolescence may underlie greater functional deficits in adolescent cannabis users than those starting use as adults. Future adequately powered studies need to address limitations of systematic quantification of cannabis use, compare well-defined groups of early and late-onset cannabis users and adopt study designs that may help address the issue of cause and effect relationship in the context of cannabis use and neurocognitive outcomes of interest. Nevertheless, current evidence indicates that adolescence is a sensitive period during which cannabis use may result in adverse neurocognitive effects that appear to show a level of permanency into adulthood, indicating a need for caution when considering the therapeutic potential of cannabis for disorders with onset in adolescence.